2020
DOI: 10.1039/d0an00510j
|View full text |Cite
|
Sign up to set email alerts
|

Direct identification of fish species by surface molecular transferring

Abstract: A surface molecular transferring strategy is the first to be utilized for the direct analysis of fish samples by mass spectrometry, and it promisingly enables fish authentication in a quick, efficient and easy mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This identification method was initially used for the identification of species of bacteria, fungi, and viruses (e.g., Claydon et al, 1996;Fenselau and Demirev, 2001), and is still widely used (e.g., Seng et al, 2010;Chalupová et al, 2014;Singhal et al, 2015). In addition, MALDI-TOF MS has been used for species identification of microalgae (Baumeister et al, 2020), microorganisms (Maier et al, 2006) and various metazoan taxa including insects (Feltens et al, 2010), fish (Volta et al, 2012;Shao and Bi, 2020), and calanoid copepods (Riccardi et al, 2012;Laakmann et al, 2013;Bode et al, 2017). Previous studies with several taxa as study subjects confirmed that MALDI-TOF MS is a reliable and fast alternative method for species identification.…”
Section: Introductionmentioning
confidence: 99%
“…This identification method was initially used for the identification of species of bacteria, fungi, and viruses (e.g., Claydon et al, 1996;Fenselau and Demirev, 2001), and is still widely used (e.g., Seng et al, 2010;Chalupová et al, 2014;Singhal et al, 2015). In addition, MALDI-TOF MS has been used for species identification of microalgae (Baumeister et al, 2020), microorganisms (Maier et al, 2006) and various metazoan taxa including insects (Feltens et al, 2010), fish (Volta et al, 2012;Shao and Bi, 2020), and calanoid copepods (Riccardi et al, 2012;Laakmann et al, 2013;Bode et al, 2017). Previous studies with several taxa as study subjects confirmed that MALDI-TOF MS is a reliable and fast alternative method for species identification.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the developed method can be a promising strategy to evaluate the change in fish muscle or other animal muscle-based foods (114). In recent years, mass spectrometric, metabolomic, and chemometric techniques have been used to investigate different fish for taxonomic classification, authentication, and quality assessment (115)(116)(117). The pre-treatment of the fish muscle samples before subjecting to spectroscopic analysis was reported to increase in effectiveness and efficacy of analysis and hence better reproducible results (118).…”
Section: Eggsmentioning
confidence: 99%
“…MALDI-TOF combined with multivariate analysis was exploited [89] for the development of a method to directly analyze fish skin or muscle tissues surface, for authentication purposes. Samples were quickly discriminated, hinting at potential future developments for the authentication of seafood in general and/or other protein food products.…”
Section: Fish and Meatmentioning
confidence: 99%